1999
DOI: 10.1046/j.1570-7458.1999.00494.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased damage by western flower thrips Frankliniella occidentalis in chrysanthemum intercropped with subterranean clover

Abstract: Suppressive effects of intercropping on Frankliniella occidentalis (Pergande) infestations have been reported in several crops. However, this study demonstrates that in year-round chrysanthemum, Dendranthema grandiflora Tzvelev, undersowing with subterranean clover, Trifolium subterraneum L., results in an increased thrips feeding damage. In a pot experiment, performed with chrysanthemum plants (cultivars Reagan and Tiger) grown with or without subterranean clover, significantly more leaves with silver and gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
(48 reference statements)
0
3
0
Order By: Relevance
“…Andow (1991) suggested that a single ecological theory could not account for the responses of all species to diversified plant systems. Further, Belder et al (1999) proposed that crop diversification influence on arthropods cannot be predicted without studying specific characteristics associated with each individual crop-pest community. Although, some of the key folivores of broccoli were reduced in vegetationally diverse habitats, endorsing its use is impractical at this time.…”
Section: Resultsmentioning
confidence: 99%
“…Andow (1991) suggested that a single ecological theory could not account for the responses of all species to diversified plant systems. Further, Belder et al (1999) proposed that crop diversification influence on arthropods cannot be predicted without studying specific characteristics associated with each individual crop-pest community. Although, some of the key folivores of broccoli were reduced in vegetationally diverse habitats, endorsing its use is impractical at this time.…”
Section: Resultsmentioning
confidence: 99%
“…Den Belder et al (1999) showed that subterranean clover is a very poor host for the western flower thrips Frankliniella occidentalis and Toapanta et al (1996) had similar results with white clover. In our field experiment, only eight T. tabaci adults and no nymphs were found on the strawberry clover in the field throughout the observation period from June to October.…”
Section: Discussionmentioning
confidence: 88%
“…Evidently, clover affects resistance of the hostplant to thrips (den Belder et al, 1999). Damage caused by T. tabaci is lower in leek intercropped with subterranean clover than in leek monocropping at the same onion thrips density (Theunissen & Schelling, 1997).…”
Section: Discussionmentioning
confidence: 99%